2021
DOI: 10.1080/2331205x.2021.1924432
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and drivers of verbal abuse among women during labour and delivery in Ndola and Kitwe districts of Zambia

Abstract: Verbal abuse during childbirth constitutes a violation of women's human rights and indicates poor maternal health care. The aim of the study was to investigate experiences and drivers of verbal abuse among women in Ndola and Kitwe health facilities. The study adopted a cross-sectional survey. Qualitative and quantitative data using questionnaires and focus group interviews were employed. The study was done in the Ndola and Kitwe districts of Zambia. The target population were women attending postnatal services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…This is consistent with a study conducted in a Midwife-Led Obstetric unit in the Tshwane district, South Africa, where women reported that midwives shout at them, label them, judge them and use rude remarks while addressing them [22]. This corresponds with a study conducted in the Ndola and Kitwe districts of Zambia, where participants indicated that they were verbally abused as they were scolded, shouted at and told hurtful words and displeasing statements and remarks [23]. Non-empathetic language is not only a concern in Limpopo Province.…”
Section: Negative Interaction With Midwivessupporting
confidence: 88%
“…This is consistent with a study conducted in a Midwife-Led Obstetric unit in the Tshwane district, South Africa, where women reported that midwives shout at them, label them, judge them and use rude remarks while addressing them [22]. This corresponds with a study conducted in the Ndola and Kitwe districts of Zambia, where participants indicated that they were verbally abused as they were scolded, shouted at and told hurtful words and displeasing statements and remarks [23]. Non-empathetic language is not only a concern in Limpopo Province.…”
Section: Negative Interaction With Midwivessupporting
confidence: 88%
“…A study in Ethiopia using the same validated tool reported a lower incidence of unfriendly care (2.2%) and a higher incidence of verbal abuse (37%) 9 . Another study in Zambia reported 11% for verbal abuse 15 . Women's perception of disrespect and abuse differ based on the sociocultural setting within and across nations.…”
Section: Discussionmentioning
confidence: 99%
“…9 Another study in Zambia reported 11% for verbal abuse. 15 Women's perception of disrespect and abuse differ based on the sociocultural setting within and across nations. This may account for the differences in the reported prevalence in both African countries despite the use of a validated tool similar to ours to assess disrespect and abuse.…”
Section: Re Sultsmentioning
confidence: 99%